LAW ENFORCEMENT AGAINST FOREST FIRE BASED ON PANCASILA IDEOLOGY - Fitri Setiyani Dwiarti (Faculty of Law-Universitas Bandar Lampung, 2022)
Forest fire law enforcement carried out by formal institutions, such as courts and the government shows a formalist, deterministic attitude, the law is understood narrowly and involutively even uprooted from the ideological/philosophical roots of Pancasila. The attitude of law enforcers who often ignore the community's sense of justice with controversial and discriminatory decisions adds to a series of law enforcement problems. local wisdom in Indonesia. This legal paper uses a philosophical approach to examine in depth the ideology of Pancasila in forest fire law enforcement. The sources of material in this paper were obtained from observations, research and literature studies. Laws, especially those relating to the Environment, fail to transform the ideological/philosophical foundation of Pancasila which has become the values ​​and spirit for the long journey of the Indonesian nation. This happens due to the lack of attention to local wisdom and national interests. The theory put forward by Robert B. Seidman, namely